ISSUES IN THE IMPLEMENTATION OF 2019 NATIONAL MINIMUM WAGE IN NIGERIA: CHALLENGES AND PROSPECTS - OKOLO, Philips O.; MICAH, Patience Ediri; BOUBAI, Joseph Jackson; OKOLO, Epebitimi Trevor (EBSU Journal of Social Sciences and Humanities, 2024)
This paper analysised the issues in the implementation 2019 national minimum wage in Nigeria with specific attention on the challenges and prospects. It employed the industrial relation theory; with focus on collective bargaining. The historical analytical method was deployed and data/analyses were chronologically presented in accordance with the objectives. It depended largely on various newspapers, journal articles, and other relevant related materials. The paper argues that Nigeria's frequent confrontations between the government and labour have posed a detrimental effect on cordial industrial relations. This is because it lacks standing machinery that is functional to center on labour economics, and determining the main issue seems to be the timing circumstances surrounding the minimum wage increase/review. It concludes that due to the government's political stance toward labour demands, industrial actions have multiplied in the country. The aforementioned indicates that the Nigerian government-labour negotiation process for new minimum wage is perceived as being unable to currently ensure the welfare of workers as expected, given the hike of inflation. The recent two hundred thousand minimum wage proposal is a clear prove. In order to comply with its obligations to the International LabourOrganisation (ILO), NLC and TUC, this paper recommends among others that the Nigerian government must implement a functioning system for the establishment and regulation of minimum wage as soon as possible in order to cushion the effects of cost of living, particularly the increase in oil price, to better the country's economic stance.